Proceedings of the 23rd Annual ACM Conference on Innovation and Technology in Computer Science Education 2018
DOI: 10.1145/3197091.3197117
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing programming assignments with CrowdSorcerer

Abstract: Small automatically assessed programming assignments are an often used resource for learning programming. Creating sufficiently large amounts of such assignments is, however, time consuming. As a consequence, offering large quantities of practice assignments to students is not always possible. CrowdSorcerer is an embeddable open-source system that students and teachers alike can use for creating and evaluating small automatically assessed programming assignments. While creating programming assignments, the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Similarly, CrowdSorcerer [31] is an embeddable tool that is used for programming assignment creation. Students come up with an assignment description according to some specifics given by an instructor.…”
Section: Related Work 21 Crowdsourcing In Cs Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, CrowdSorcerer [31] is an embeddable tool that is used for programming assignment creation. Students come up with an assignment description according to some specifics given by an instructor.…”
Section: Related Work 21 Crowdsourcing In Cs Educationmentioning
confidence: 99%
“…Another way to alleviate quality issues is peer reviewing, as with the multiple-choice questions in PeerWise [12] and programming assignments in CrowdSorcerer [31]. Studies have shown that the quality of peer reviewed exercises is good [13,19], even when both the creators and the reviewers are from the same crowd of students.…”
Section: Quality Of Crowdsourced Contentmentioning
confidence: 99%
“…In addition to weekly programming assignments, the courses used a crowdsourcing tool called CrowdSourcerer [15] that allows the students to create programming assignments related to a certain topic of the course, e.g. loops.…”
Section: Context and Datamentioning
confidence: 99%
“…My research extends the previous work regarding the use of CrowdSorcerer [6], and the quality and usability of the programming assignments created with the tool [7]. My research also strives to generalize the results and working solutions of existing educational tools that utilize crowdsourcing in computer science education.…”
Section: Introductionmentioning
confidence: 65%